Rice Field Insect Pests During the Rice Growing Seasons in Two Areas Of Hathazari, Chittagong (Bangladesh Journal of Zoology, 2012)
A survey of rice field insect pests was conducted during the rice growing seasons in two areas of Hathazari, Chittagong for a period of one year to prepare a preliminary list of rice field insect pests, in three rice growing seasons (Boro, Aus  and Aman). During the study period 35 species belonging to 30 genera under 13 families under four economically important insect orders were recorded. These were: order Hemiptera- five families with 14 species, order Orthoptera- four  families with nine species, order Lepidoptera- three families with 11 species and order- Coleoptera- one family with one species. On the basis of numerical records  of the rice field insect pests, the ranking of the seasons was: Boro > Aman > Aus;of the stages was: Seedling > Transplanting > Flowering; of the orders was:   Hemiptera > Orthoptera > Lepidoptera > Coleoptera; and of the spots was: Spot 2 > Spot 1. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12898 Bangladesh J. Zool. 40(1): 89-100, 2012